Comparison of JAKABA (Eternal Luck Fungus) Fertilizer Production Methods and Fermentation Success - Rafeah Husni; Nur Asiah Mtd (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Sustainable agriculture requires innovations in environmentally friendly organic fertilizers to maintain soil fertility and reduce dependence on inorganic fertilizers. One such innovation is Jakaba (Jamur Keberuntungan Abadi), a liquid organic fertilizer produced through the fermentation of organic materials involving microbial activity. This study aims to compare three methods of Jakaba production, namely the firewood method, gas stove method, and rice water method, in terms of fermentation success. This research was conducted on April 06 at the Biology Laboratory yard of STAIN Mandailing Natal using a simple experimental method through direct observation. The observed parameters included growth rate, mycelium thickness, Jakaba quality, production cost, material availability, and processing procedure. The results showed that the firewood method produced the most optimal Jakaba growth, reaching approximately ±11 cm in height with thick mycelium and the best quality, while the gas stove method did not produce any growth, and the rice water method resulted in slow growth of about ±3 cm after three weeks of fermentation. Therefore, the firewood method is considered the most effective method for Jakaba production.